2016
DOI: 10.1080/19315260.2016.1258605
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic, Nutraceutical, and Organoleptic Performances of Wild Herbs of Ethnobotanical Tradition

Abstract: Despite the growing interest for wild herbs as nutraceutical food there is a lack of information on how to grow them. Ten wild herbs were collected in natural and/or anthropized environments and assessed for their agronomic performance as fresh-cut (or ready-to-eat) leafy vegetables and their nutraceutical and organoleptic attributes. Seed dormancy prevented acceptable germination in many species. However, a physiological seed treatment (soaking with sodium hypochlorite followed by incubation for 3 mo at 4°C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Most of these species are an integral part of local cuisines and are traditionally used for culinary and medicinal purposes [16][17][18]. Recently, the commercial cultivation of such species has gained interest both by farmers and consumers, and several studies have reported the potential of using wild edible species in sustainable cropping systems for the production of high value-added products due to increased health beneficial effects [19][20][21][22]. Considering that these species are usually collected in the wild or confronted as weeds within the fields, there is a lack of information regarding the best practice guides that should be applied to ensure high yields without compromising the quality and food safety of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these species are an integral part of local cuisines and are traditionally used for culinary and medicinal purposes [16][17][18]. Recently, the commercial cultivation of such species has gained interest both by farmers and consumers, and several studies have reported the potential of using wild edible species in sustainable cropping systems for the production of high value-added products due to increased health beneficial effects [19][20][21][22]. Considering that these species are usually collected in the wild or confronted as weeds within the fields, there is a lack of information regarding the best practice guides that should be applied to ensure high yields without compromising the quality and food safety of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Although MD is sustainable in its conception, the recently identified social and economic trends make it necessary to reevaluate the whole food chain, including crop production, food production, and consumption, also considering environmental, nutritional, economic, and social aspects [106]. Recently, several reports highlighted the importance of commercial cultivation of wild edible greens within the framework of sustainable management of native Mediterranean species and the exigent need for an increase in agrobiodiversity in farming systems, which is threatened by ongoing climate change and monocropping [108][109][110][111]. According to a recent report published by the Food and Agriculture Organization of the United Nations, only nine crops contribute 66% of the global total production of food [37].…”
Section: Mediterranean Diet and Agrobiodiversitymentioning
confidence: 99%
“…However, considering that the common practice so far has been to collect these species from the wild raises major concerns regarding the threat of genetic erosion and the ecosystems' disruption due to irrational harvesting. For this purpose, gaining knowledge about the commercial cultivation of wild edible species is necessary to establish a valid and sustainable value chain and allow their integration into the existing farming systems [13][14][15].…”
Section: Introductionmentioning
confidence: 99%